The Effect of Applying Tangram Media on the Mathematics Learning Outcomes of First-Grade Students at MI Adabiyah 2 Palembang - Dita, Etiara Neva; Al Ihwanah; Ayu Nur Shawmi; Maryamah; Ines Tasya Jadidah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the effect of applying tangram media on the mathematics learning outcomes of first-grade students at MI Adabiyah 2 Palembang. The research type used is quantitative with a quasi-experimental method and a nonequivalent control group design. Data collection techniques include observation, tests, and documentation. The research sample consists of two classes: class I.3 as the experimental group using tangram media, and class I.4 as the control group using conventional methods. The analysis results show that the average posttest score of the experimental class is higher than that of the control class, with average pretest scores of 59.25 and 48.84, and posttest scores of 83.79 and 64.08 for each class, respectively. Statistical testing shows a significance value of 0.000, indicating a significant effect of using tangram media on students' mathematics learning outcomes. These findings emphasize that tangram media is effective in improving the understanding of flat geometry concepts through visual, kinesthetic, and interactive approaches. Therefore, the use of tangram media is highly recommended as an enjoyable and meaningful learning strategy at the elementary education level.